Large‐cohort humanized NPI mice reconstituted with CD34+ hematopoietic stem cells are feasible for evaluating preclinical cancer immunotherapy. Issue 4 (8th March 2022) - Xu, Xiongfei; Gu, Haihui; Li, Hongwei; Gao, Suizhi; Shi, Xiaohan; Shen, Jing; Li, Bo; Wang, Huan; Zheng, Kailian; Shao, Zhuo; Cheng, Peng; Cha, Zhanshan; et al.
Abstract: Cancer immunotherapy has achieved impressive therapeutic effects in many cancers, while only a small subset of patients benefit from it and some patients even have experienced severe toxicity. It is urgent to develop a feasible large‐cohort humanized mouse model to evaluate the pre‐clinical efficacy and safety of cancer immunotherapy. Furthermore, developing potentially effective combination therapy between cancer immunotherapy and other therapies also needs humanized mouse model to adequately mimic clinical actual setting. Herein, we established a humanized mouse model engrafted with less human CD34 + HSCs than ever before and then evaluated reconstitution efficiency and the profiles of human immune cells in this humanized mouse model. Also, this humanized mouse model was used to evaluate the preclinical efficacy and safety of cancer immunotherapy. For each batch of CD34 + HSCs humanized mouse model, a relatively‐large cohort with over 25% human CD45 + cells in peripheral blood was established. This humanized mouse model could efficiently reconstitute human innate and adaptive immune cells. This humanized mouse model supported patient‐derived xenograft tumor growth and tumor infiltration of PD‐1 + human T cells. Furthermore, therapeutic efficacy, re‐activation of tumor‐infiltrated T cells, and side effects of checkpoint blockade therapy could be monitored in this humanized mouse model. Human T cells from this humanized mouse model were successfully engineered with CD19‐CAR. CD19 CAR‐T cells could effectively deplete B cells and suppress tumor growth of acute lymphoblastic leukemia in vivo in this humanized mouse model. This humanized mouse model also could be used to demonstrate the efficacy of bispecific antibodies, such as anti‐CD19/CD3. Overall, our work provides a feasible large‐cohort humanized mouse model for evaluating a variety of cancer immunotherapy approaches including checkpoint inhibitors, adoptive cell therapy, and bispecific antibody therapy, and demonstrates that human T cells from this humanized mouse model possess anti‐tumor activities in vitro and in vivo.